Hegemony and heteronormativity: homonormative discourses of LGBTQ activists about lesbian and gay parenting - Lasio, D. (2018)
LGBTQ activists have a crucial role in fighting sexuality-based discrimination. However, homonormativity can lead activists to adhere to hegemonic heteronormativity, thus threatening their efforts to widen the concept of family. Drawing on the Gramscian notion of hegemony, this paper analyzes the notion of heteronormativity and its homonormative facet as a form of hegemony that impacts activists, sustaining the premises of heteronormativity and seeking inclusion within such norms. This research investigates the hegemonic heteronormative assumptions that endure in the discourses of Italian LGBTQ activists when they talk about lesbian and gay parenting. Findings highlight the presence of heteronormative traces in their discourses, namely in terms of access to reproduction, the parents’ place within the regime of gender and the right standards for child rearing. Hegemonic heteronormativity appears in multiform ways, and as largely consensual even to those it more directly oppresses, making it difficult to detect and therefore to deconstruct.